The radio in Spain - Arboledas, Luis (Javnost (Ljubljana), 2014)
The democratisation of media depends not only on legal reforms and economic changes introduced into their structure, but also the biasing effect the dominant political culture can exert in this process. As seen in the Spanish radio industry, changes made since the beginning of the political transition period are purely formal because they remain deep traits inherited from the Franco dictatorship such as clientelism and political instrumentalisation. This article analyses the evolution of private radio and relates the survival of typical values of the dictatorship with the persistence of the political culture of Francoism, accepted and internalised by the new democratic regime.
Keywords: mass media; množični mediji; politična kultura; democracy; demokracija; Spain; Španija